How Students Communicate in Citizen Science Project to Build Knowledge - Hamidah, Nur; Hidayat, Topik; Sriyati, Siti; Gusti, Utari Akhir (FKIP Universitas Lampung, 2024)
Abstract: This research aims to provide information about several ways students communicate to build knowledge in citizen science projects (CSP). As the term “citizen science” applies to science that involves people who are not professional scientist to attract wider public participation in scientific research, leading to the overall advancement of scientific knowledge. Quantitative descriptive research was conducted by implementing as well as observing CSP activities in class and completing surveys to 36 students who had participated in CSP. The findings of this research show that most students (83%) received passing grades above 70 score, the minimum passing criteria. The percentage of completion of learning outcomes falls into the very effective category (n>80%). This means that CSP learning is able to build knowledge through the communication activities trained in it. On average, students responded strongly agree-agree (87.3%) that the communication carried out in CSP builds their knowledge. There are five CSP activities that involve communication between students, schools’ community, teacher and expert scientist. The five main activities of CSP, namely (1) focus group discussion (FGD) with scientists, (2) conducting projects, (3) presenting project results to scientists, (4) reporting project results, (5) and finally publishing project results project. The implications of this research inform several communication activities that can be carried out to build knowledge in learning through CSP. Keywords: communication, knowledge building, citizen science project (CSP)DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp1-13